Instrumentos jurídicos para a organização das atividades agrárias da comunidade kalunga do engenho II - SIQUEIRA, Roberta Cristina de Morais (2012)
The research that follows discusses the way in which agrarian economic activities are organized in the community Kalunga of Engenho II, a collectivity of people living in the northeastern of Goiás state and has quilombola ancestry. It started from the assumption that the Association Kalunga of Cavalcante is a suitable instrument for economic and social development of the people and that impedes their progress does not relate to this organizational form, but an entire social structure that comes from the neo-liberal capitalism. Was used as a theoretical-methodological proposal to analyze and characterize the community through the established legal order in conflict with the law as an instrument of empowerment of local communities and social movements. To reach the proposed objective, we seek the theoretical reflections of the jurist and sociologist Boaventura de Sousa Santos, who proposes a reinvention of the right, using it as an instrument of transforming society through the action of social groups, and many other authors of reference, which are scattered throughout the body of research.